Adaptation of The Gratitude Questionnaire (GQ-6) In Indonesian High School Students - M. Ahkam Alwi; Nurfitriany Fakhri; Wawan Kurniawan (Journal of Educational, Health and Community Psychology, 2023)
The study of gratitude has begun to develop in Indonesia. Along with this development, there is a need for a measurement tool that can explain the concept of gratitude. This study aims to adapt the gratitude questionnaire (QG-6) to the Indonesian language. The study was conducted on 275 high school students in Surabaya City. The results of confirmatory factor analysis obtained 5 adequate items that have a factor loading value (> 0.5). Measurement model fit (p < 0.01, RMSEA =. 0.08, GFI = 0.98, CFI = 0.99, SRMR = 0.02.) Construct reliability on QG-5 is 0.813